Impact on performance and emissions of the aspiration of algal biomass suspensions in the intake air of a direct injection diesel engine. (1st February 2020) - Wei, Xinyu; Hellier, Paul; Baganz, Frank
Highlights: Algae biomass was aspirated as water suspensions into a diesel engine. Engine work output increased with the concentrations of biomass above 7.5% w/w. Aspiration of algal biomass suspension resulted in a reduction of NOx emission. Thermal efficiency decreased with aspiration of algae biomass suspension. Abstract: Recently, the production of sustainable biofuels from algal biomass has gained significant attention and been investigated as a potential replacement of fossil fuel. However, existing downstream processes for producing biodiesel from algae cells are complex, highly energy-intensive, and have high economic and environmental cost. Therefore, this work introduces an alternative and novel method of utilizing the energy content of microalgae that precludes lipid extraction by aspirating wet algal biomass suspensions directly into the intake air of an internal combustion engine. For all engine experiments, powdered algae cells were prepared as slurries at different biomass concentrations. The impacts of (i) varying the biomass concentration with constant suspension injection flowrate into the engine intake and (ii) varying suspension injection flowrate with constant biomass concentration were investigated. A correlation between engine work produced during combustion and algal biomass aspiration was found. At constant flowrate and greater than 5% biomass concentrations, an increase of energy release during combustion from the aspirated algae could be observed. However, the aspiration of low concentration biomass suspension produced a negative impact on engine performance relative to water-only aspiration. The engine exhaust gas of nitrogen oxides (NOx) was reduced for all algae suspension tests relative to diesel-only combustion. However, the carbon monoxide (CO) emission level was much higher relative to diesel-only tests at high biomass concentrations and injection flowrate. These findings demonstrate the possibility of utilising the energy content of algal biomass in combustion without lipid extraction, with added benefits of reducing NOx emissions.